Impact Of Audit Committee Characteristic On Firm Performance: Listed Companies In Sri Lanka - Muraleetharan, P.; Dopika, K. (Faculty of Arts and Culture South Eastern University of Sri Lanka, 2025)
The Audit Committee plays a vital role in overseeing the audit process, the company’s system of internal controls, financial risk management, and compliance with laws and regulations. This study explores the impact of audit committee characteristics on firm performance, based on an empirical analysis of companies in Sri Lanka. Firm performance was measured using Tobin’s Q, Return on Assets (ROA), and Return on Equity (ROE). The characteristics of audit committees were assessed through three proxies: Audit Committee Size (ACS), Audit Committee Independence (ACI), and Audit Committee Meetings (ACM). The study utilized data from 49 listed companies in Sri Lanka, covering the year from 2019 to 2023. A quantitative research method was employed, with data collected from annual reports of the selected companies. The results indicate that Audit Committee Independence (ACI) has a positive impact on both ROA and Tobin’s Q, suggesting that greater independence within audit committees enhances oversight and improves firm performance. In contrast, Audit Committee Size (ACS) shows a negative relationship with both ROA and Tobin’s Q. Additionally, Audit Committee Meetings (ACM) are negatively associated with ROE and ROA, while showing an insignificant effect on Tobin’s Q. These findings have important implications for policymakers, providing valuable insights for strategic policy formulation and implementation aimed at enhancing corporate governance practices, thereby contributing to income and wealth maximization.
Keywords: Audit committee meeting; Audit committee size; ROA and ROE